Strategi Penguatan Resiliensi Usaha melalui Literasi Manajemen Keuangan Berbasis Artificial Intelligence dan Formalisasi Legalitas pada Sektor UMKM di Kelurahan Batu Besar, Kota Batam - Mohamad Hisam; Eliska Sani; Shanry Asriany Hansen; Hedison Permata; Enay Sunarya; Rica Fitri Susanti; Septa Diana Nabella; Andi Hidayatul Fadlilah (CV. Aksara Global Akademia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy of Batam City, particularly in the Batu Besar sub-district, Nongsa. However, their development is constrained by low financial literacy and a lack of formal legality. This community service program (KPM) aims to strengthen MSME business resilience through a dualpillar strategy: digital financial literacy training utilizing the Artificial Intelligence-based application FinSense AI and formal legality assistance through the issuance of Business Identification Numbers (NIB) via the Online Single Submission (OSS) system. The service method involved baseline mapping, interactive workshops, door-to-door intensive mentoring, and evaluation. The program was conducted from June 6 to July 4, 2026, involving 21 students and 4 supervising lecturers targeting MSMEs in RW 08, Kelurahan Batu Besar. The results showed a significant increase in financial literacy, with 34 MSMEs actively adopting FinSense AI to separate personal and business finances and monitor cash flow health automatically. Furthermore, 35 MSMEs successfully obtained formal legal status with the issuance of NIB. The integration of technology-based financial discipline and official legal protection successfully minimized financial risks and opened broader access to formal financial institutions and government programs, significantly enhancing local MSME business resilience.